2009
DOI: 10.1088/0031-9155/54/16/n01
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of Cerenkov light generation from positron-emitting radiotracers

Abstract: Radiotracers labeled with high-energy positron-emitters, such as those commonly used for positron emission tomography (PET) studies, emit visible light immediately following decay in a medium. This phenomenon, not previously described for these imaging tracers, is consistent with Cerenkov radiation and has several potential applications, especially for in vivo molecular imaging studies. Herein we detail a new molecular imaging tool, Cerenkov Luminescence Imaging, the experiments conducted that support our inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
380
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(386 citation statements)
references
References 13 publications
6
380
0
Order By: Relevance
“…Although radiation luminescence from charged particles has been used successfully for in vivo optical imaging [4,5], to the best of our knowledge, its application beyond imaging has not yet been explored. In this proof-of-concept report, we demonstrated that the phenomenon of radiation lumines- cence could be used for photoactivatable chemical conversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although radiation luminescence from charged particles has been used successfully for in vivo optical imaging [4,5], to the best of our knowledge, its application beyond imaging has not yet been explored. In this proof-of-concept report, we demonstrated that the phenomenon of radiation lumines- cence could be used for photoactivatable chemical conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been growing interest in the use of photons from Cherenkov radiation for optical imaging [4][5][6][7][8][9][10][11][12] and for excitation of quantum dots and fluorophores in vivo [6,8]. Charged particles such as β + and β − which are generated from radioactive isotope decay can result in visible light with a broad energy range (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been 80 years since its first observation [1], surprisingly little attention was given to the importance of the quantum nature of the charged particles producing the radiation. Since its discovery, the Čerenkov effect has become a fundamental part of many fields [2]: Devices like the ring-imaging Čerenkov detector are used for cosmic radiation measurements [3,4], while other implications also suggest novel acceleration methods [5], and even an unusual imaging tool in biology [6,7]. Because of the fundamental nature of ČR, it is found in many different physical systems, such as in nonlinear optics [8][9][10][11], it is used in the design of quantum cascade lasers [12], and it is predicted to yield the generation of entangled photon pairs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…18 In this regard, Cerenkov luminescence imaging (CLI) is a promising optical-based method based on the unique property of photo-emission from luminescent radionuclides when the charged particles (mostly β + ) travel through water with velocities faster than the speed of light. 18,19 In spite of many attempts to use PET radionuclides, such as 64 Cu, 68 Ga and 124 I for CLI-based optical imaging, 20 the quantitative relationship between PET and CLI imaging has not yet been firmly established, though such knowledge is required for future CLI-based imaging in clinical applications.…”
Section: Introductionmentioning
confidence: 99%